Literary section: An Introduction - Fotta, Martin; Sabino-Salazar, Mariana (Romano džaniben, 2021)
Brief introductoryg notes on the section presenting Romani writers from Latin America, who contributed to the thematic double issue of Romano džaniben with short examples of their prose and poetry: Jorge Emilio Nedich, Voria Stefanovski, Juan Luis Aguilera.
Keywords: Literatura; Romani literature; Latin America